PENGENDALIAN PENDAPATAN PADA TITIK TRANSISI TAHAP LIFE CYCLE: STUDI KASUS PERUSAHAAN MANUFAKTUR - Herawati, Iis Dewi (LPPM STMIK WIT, 2022)
Corporations pass every stage of their life cycles through different ways. At each point of these stages a company has the possibility to turn into decline. When this occurs, a company has the incentive to manage earnings in order to maintain its performance reflected in reported earnings. The objective of this study is to examine whether earnings management choices are different in corporate life cycles from growth to mature and mature to stagnant. The differences in earning management behaviour were indicated by negative and positive discretionary accruals. The sample was taken from manufacturing firms listed on the Indonesia Stock Exchange (2006 to 2013) in different life stages. The results show that firms in growth-mature and mature-stagnant did manage earnings through discretionary accruals, as indicated by significant differences as compared to those in other corporate life cycles.